Effects of Regulatory Focus and Emotions on Information Preferences: The Affect-as-Information Perspective - Wang, Xiaomei; Zheng, Quanquan; Wang, Jia; Gu, Yangli; Li, Jiongying (Frontiers in Psychology, 2020)
This study explored the effects of regulatory focus and emotions on information preferences. We examined the influences of regulatory focus and emotions on information selection preferences(experiment 1), implicit information preferences(experiment 2). The findings revealed that, in the promotion-focused condition, individuals preferred hedonic information (vs. functional information)when they were happy(vs. sad). However, the emotions’ effects on information preferences were attenuated in the promotion-focused condition. In experiment 3, we tested whether regulatory focus and salient emotions influence information preferences. The results suggested that regulatory focus and salient emotions had no significant interactive effect on information selection preferences but had a significant interactive effect on implicit preferences. These results further our understanding of the psychological dynamic mechanism involved in information preferences, which improves the affect-as-information theory.